Effect of Cognitive Demand on Functional Visual Field Performance in Senior Drivers with Glaucoma - Gangeddula, Viswa; Ranchet, Maud; Akinwuntan, Abiodun E.; Bollinger, Kathryn; Devos, Hannes (Frontiers in Aging Neuroscience, 2017)
Purpose: To investigate the effect of cognitive demand on functional visual field performance in drivers with glaucoma. Method: This study included 20 drivers with open-angle glaucoma and 13 age- and sex-matched controls. Visual field performance was evaluated under different degrees of cognitive demand: a static visual field condition (C1), dynamic visual field condition (C2), and dynamic visual field condition with active driving (C3) using an interactive, desktop driving simulator. The number of correct responses (accuracy) and response times on the visual field task were compared between groups and between conditions using Kruskal-Wallis tests. General linear models were employed to compare cognitive workload, recorded in real-time through pupillometry, between groups and conditions. Results: Adding cognitive demand (C2 and C3) to the static visual field test (C1) adversely affected accuracy and response times, in both groups (p< 0.05). However, drivers with glaucoma performed worse than did control drivers when the static condition changed to a dynamic condition (C2 vs C1 accuracy; glaucoma: median difference (Q1-Q3) 3 (2-6.50) vs controls: 2 (0.50-2.50); p = 0.05) and to a dynamic condition with active driving (C3 vs C1 accuracy; glaucoma: 2 (2-6) vs controls: 1 (0.50-2); p = 0.02). Overall, drivers with glaucoma exhibited greater cognitive workload than controls (p = 0.02). Conclusions: Cognitive demand disproportionately affects functional visual field performance in drivers with glaucoma. Our results may inform the development of a performance-based visual field test for drivers with glaucoma.